The Influence of Price and Online Customer Reviews on Fashion Purchase Decisions with Product Quality as a Mediating Variable on TikTok Shop - Viniyati Maftuchach; Yatita Ratu Amanda; Lela Nurlaela Wati (Dinasti Publisher, 2026)
This study aims to examine the role of product quality in mediating the influence of prices and online customer reviews on fashion product purchase decisions among TikTok Shop users in Jakarta. A quantitative approach was used in a survey method of 160 respondents who were selected using purposive sampling techniques. Data analysis was carried out using Structural Equation Modelling (SEM) with the help of SmartPLS software. The results of the study show that price has a positive and significant effect on product quality and purchase decisions. Online customer reviews have a negative and significant direct effect on purchase decisions. In addition, product quality significantly mediates the effect of price on purchase decisions. Meanwhile, product quality does not significantly mediate the influence of online customer reviews on purchase decisions.